2014
DOI: 10.1007/s10554-014-0545-2
|View full text |Cite
|
Sign up to set email alerts
|

Coronary atheroma composition and its association with segmental endothelial dysfunction in non-ST segment elevation myocardial infarction: novel insights with radiofrequency (iMAP) intravascular ultrasonography

Abstract: Little is known of the relationship between coronary atheroma composition and corresponding endothelial dysfunction. We tested the hypothesis that segmental epicardial vasoreactivity relates to atheroma composition in patients with non-ST segment elevation myocardial infarction (NSTEMI) in vivo. In 23 NSTEMI patients referred for coronary angiography, a non-culprit vessel underwent intracoronary salbutamol (0.30 μg/min) provocation during automated IVUS pullback. A 40 MHz rotational IVUS catheter delivered rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…multitransmit radiofrequency) and software allow improved visualization of the coronary vessel wall, permitting a more detailed analysis of wall remodeling than was previously possible. The type of coronary wall remodeling (concentric vs. eccentric) may play an important role in local plaque progression or acute coronary syndrome [36]. Prior studies report that acute coronary syndromes tend to occur in vessels with angiographically mild disease [6].…”
Section: Discussionmentioning
confidence: 99%
“…multitransmit radiofrequency) and software allow improved visualization of the coronary vessel wall, permitting a more detailed analysis of wall remodeling than was previously possible. The type of coronary wall remodeling (concentric vs. eccentric) may play an important role in local plaque progression or acute coronary syndrome [36]. Prior studies report that acute coronary syndromes tend to occur in vessels with angiographically mild disease [6].…”
Section: Discussionmentioning
confidence: 99%
“…In general, lipid plaque is formulated through the influx of atherogenic inflammatory cytokines and oxidative stress, causing endothelial dysfunction (21). This mechanism is supported by another study which demonstrated severer endothelial dysfunction at target lesion harboring a great amount of necrotic core materials (20,22). Since the endothelium regulates vascular tone (8), lipidic atheroma with endothelial dysfunction may cause insufficient vascular response during hyperemic status, potentially leading to a greater delta-FFR.…”
Section: Discussionmentioning
confidence: 85%
“…Recent studies have reported a potential role of plaque vulnerability in reduced FFR (4,20). However, the mechanism behind this observation remains to be fully determined yet.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used radiofrequency IVUS derived from a 20 MHz IVUS catheter and applying the proprietary analysis software called VH‐IVUS . Available data with iMAP‐IVUS were limited to describing plaque composition, without the proposition of an algorithm for phenotype classification .…”
Section: Discussionmentioning
confidence: 99%